DWT 2019
DOI: 10.5004/dwt.2019.23554
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption - a case study of hexavalent chromium removal with raw pomegranate peel

Abstract: Biosorptive removal of heavy metals from water is an eco-friendly green technology. In this study, raw pomegranate (Punicagranatum L.) peel (RPP), without any modification or activation, was used as biosorbent for the removal of chromium (Cr(VI)). The influence of operating parameters such as pH, contact time, temperature and concentration of Cr(VI) were studied in batch mode. A maximum removal of 100% was achieved for a Cr(VI) solution of concentration 20 mg/L at an optimum pH and temperature of 2 and 313 K r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…K L values reported in the aforementioned pertinent literature were less than unity, except for the K L = 2.76 reported by Giri, et al [13]. The dimensionless separation factor, R L , which is used to evaluate the feasibility and applicability of the process was found to be less than unity in the current study, as well as in the result presented by Salam, et al [14] and Ben-Ali, et al [19]. This finding is an indication of a favorable adsorption (since 0 < R L < 1).…”
Section: • Ln a T C Esupporting
confidence: 45%
See 4 more Smart Citations
“…K L values reported in the aforementioned pertinent literature were less than unity, except for the K L = 2.76 reported by Giri, et al [13]. The dimensionless separation factor, R L , which is used to evaluate the feasibility and applicability of the process was found to be less than unity in the current study, as well as in the result presented by Salam, et al [14] and Ben-Ali, et al [19]. This finding is an indication of a favorable adsorption (since 0 < R L < 1).…”
Section: • Ln a T C Esupporting
confidence: 45%
“…Other authors also reported the presence of carbon, oxygen, nitrogen, and hydrogen as the major constituents of PMPP [13,19]. However, asides from the main constituents, traces of potassium, calcium, copper, zinc, manganese, iron were also observed by [13,14].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 92%
See 3 more Smart Citations